The Effect of Financial Literacy on Investment Interest with Financial Awareness as a Mediating Variable Among Students at Padang State University - Afrizal, Arif Dwi; Afdal, Zul (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines the role of financial awareness as a mediating variable in the relationship between financial literacy and investment interest among students of the Faculty of Economics, Padang State University. A quantitative approach was used with path analysis techniques to test the direct and indirect effects between variables. A sample of 344 students was selected using proportional random sampling from a total population of 31,425 students. Data collection was conducted using a Likert scale questionnaire and analyzed using SPSS version 25. The results showed that financial literacy had a positive and significant direct effect on investment interest. Financial awareness also significantly influenced students' investment interest. In addition, financial awareness was proven to play a role as a mediating variable in the relationship between financial literacy and investment interest, as indicated by the Sobel test with a significance value below 0.05. The total contribution of financial literacy and financial awareness in explaining variations in investment interest reached 90.71%. However, this figure needs to be understood carefully so as not to give an exaggerated impression of the model's strength. More than just statistical results, these findings reveal that students with high levels of financial literacy tend to have stronger financial awareness, which simultaneously shapes positive mindsets and attitudes toward investment. This shows that financial understanding not only plays a role as technical knowledge, but also as a psychological and behavioral foundation for wise financial decision-making. The practical implications of these findings emphasize the importance of strengthening financial literacy education programs and increasing financial awareness from an early age, both through academic curricula and external training. These efforts are expected to encourage students to become smart, rational young investors who are prepared to face risks in an informed manner.